Faktor Faktor yang Mempengaruhi Ketidakpatuhan Minum Obat pada Pasien Skizofrenia di Yayasan Galuh Kota Bekasi Tahun 2016 - Ahmad Farid Umar; Elwindra Elwindra; Yemima Yemima (STIKes Persada Husada Indonesia, 2017)
Schizophrenia is one of the more severe types of mental disorder where the patient is unable or confused to distinguish between fact and fiction. Disobedience of patients to take medication is a major factor in the difficulty of recovery, in addition to the incontinence of environmental conditions. The purpose of this study was to determine the factors that influenced medication non-adherence in schizophrenic patients. The research was conducted at Galuh Kota Bekasi Foundation in 2016. This research used qualitative design with case study approach. The variables in this study focused on medication non-adherence patients seen from the patient's own factors, family factors, and health workers factors. Data collection by in-depth interviews, observation, and document reviews. Observations were made in the rehabilitation room, special isolation room, hall and treatment room of Galuh Foundation. The results showed that patients themselves felt saturated taking medication because the effects of the medications caused the bodies to become stiff and always asleep. Another factor is the lack of support from family to take medication regularly, family and society still giving a negative stigma to the sick family member with rare visits to patients undergoing treatment at Galuh Foundation. The number of workers at Galuh Foundation is still limited in administering medications in large quantities to patients needing treatment.